PENGARUH PENYULUHAN GIZI DENGAN PERUBAHAN PERILAKU SARAPAN PAGI SISWA SEKOLAH DASAR - Nindrea, Ricvan Dana (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Basic Health Research Data years 2010-2013 showed an increased prevalence of nutritional status (BMI for Age) with a category of thin 7,6%, while in 2013 increased to 11,2%. Total of 16 provinces have prevalence thin School Age Children above the national prevalence, one of the province are the West Sumatra Province. One of the causes of the incident is school age childrens food consumption is not good. This study aims to determine the effect of nutrition counseling to behavior change of breakfast in elementary school students. This type of research with pre experimental study. The research approach using a design one group pre and post test design. The study was conducted in 05 Elementary Schools of South Solok District. The research was conducted from November 2015 to May 2016. The population in this study all students in fourth and fifth grade 05 Elementary School South Solok District. These samples included 58 people with the sampling technique stratified random sampling. Data analysis was performed using mutivariat General Linear Model (GLM) Repeated Measures analysis. The survey results revealed an increase in the average behavior before and after counseling 3 times. Average behavior before the counseling 18 ± 4,2, post test I increased to 25 ± 4,4, post test II increased to 30 ± 2,2 and post test III increased 37 ± 3,5. Based on the analysis of the GLM Repeated Measures according breakfast behavior known that increasing breakfast behavior has occurred in the post test I (p = 0,000), as well as post test II and III (p = 0,000).